The loss of a dream: parents raising an autistic child - Ritchie, Tiffany L. (Kansas State University, 2009)
This study explored the parents’ perspective of having a child with Autism living in the home. Specifically, the researcher was looking to explore the attachment style between the parent and child, as well as the process of the parents’ changing their expectations of their child, from the expectation of raising a normal child to raising a child with Autism. In order to understand the experience of both families interviewed, the researcher, through semi-structured, qualitative interviews, interviewed each parent separately. A multiple case study approach was used in order to allow for comparison within each family. Methods for analyzing the data included coding the data, so that the data could be analyzed from the individual interviews and also analyzed based on family response. For the parents interviewed in the study, four themes emerged that were similar for all parents. These themes included the diagnosis process, the differences in attachment before and after their child was diagnosed, the changing expectations of themselves, each other and their diagnosed child, and the parents’ views on getting professional help, such as therapy. Both families shared the experience of confusion during the diagnostic process, especially confusion surrounding the cause and prognosis of Autism. All parents in the study illustrated the attachment injury after their child’s diagnosis, in addition to when the child began showing the classic signs of Autism. The study also found that each parent’s expectations changed from higher ones of themselves, spouse and diagnosed child to more moderate and low expectations of their spouse and diagnosed child. Last, all parents interviewed expressed that seeking therapy would have helped them deal with the diagnostic process and better cope with having a child with Autism. It is believed by the researcher that these themes have emerged because of the families’ shared experience of raising an Autistic child.
Keywords: Autism; Caring for an Autistic Child; Parents as Caregivers; Pauline Boss Ambiguous Loss; Attachment Theory; Family Therapy with parents of special needs children; Education, Special (0529); Health Sciences, General (0566); Health Sciences, Mental Health (0347); Health Sciences, Public Health (0573); Psychology, General (0621); Psychology, Psychobiology (0349); Sociology, Individual and Family Studies (0628)